Chemical-switching strategy for the production of green biofuel on NiCo/MCM-41 catalysts by tuning atmosphere. (1st May 2022) - Lei, Xiaomei; Du, Xiangze; Xin, Hui; Chen, Xiaoqin; Yang, Huiru; Zhou, Linyuan; Zeng, Yan; Zhang, Hualong; Tian, Yunfei; Li, Dan; Hu, Changwei
Highlights: The surface properties of NiCo/MCM-41 can be effectively tuned by pretreatment gas. The largest amount of Lewis acid on NiCo/MCM-41-H promoted the HDO pathway. NiCo/MCM-41-H can effectively convert jatropha oil into green biofuel. Abstract: NiCo bimetallic catalyst was one of potential candidates used toward the hydrodeoxygenation of vegetable oils. However, there is still lack for digging out the relationship between micro-structure pretreated by various atmosphere and its catalytic performance. To hunting the relationship, NiCo/MCM-41 precursor was synthesized via the conventional co-impregnation method, and further pretreated by different atmospheres, including NH3, CH4 /H2 and H2 in order to tune the particle size, active component dispersion, and acid properties of the catalysts. NiCo/MCM-41-H pretreated by H2 exhibits superior catalytic performance (65.8 wt% biofuel yield and 98.2% C12 -C18 alkanes selectivity) on converting jatropha oil than that by NH3 and by CH4 /H2 . For comparison, the NiCo/MCM-41-H shows the smallest NiCo alloy grains, the smallest amount of strong acid, the lowest Brønsted acid/Lewis acid ratio, and the most uniform dispersion of Ni and Co. All the distinct surface properties of NiCo/MCM-41-H reasonably account for high efficiency in hydrodeoxygenation of jatropha oil. The work reveals the relationship between NiCo bimetallic catalyst structure and its hydrodeoxygenation performance, and provides a robust pretreatment method for tuning the surface properties to improve its catalytic performance for converting biomass oils into green biofuel.